Fear of missing out, social media use and alcohol consumption in college students. A path analysis model - Gómez-Martínez, Mario; Rosa-Alcázar, Ana Isabel (Anales de Psicología / Annals of Psychology, 2024)
Problematic social media use (PSMU) and excessive alcohol consumption are two of the most prevalent problems in college students. Fear of Missing out (FoMO) is defined as a pervasive apprehension that others might be having rewarding experiences from which one is absent and by the desire to stay continually connected to what others are doing (Przybylski et al., 2013). This construct has been linked to these behaviors. The study aims to analyze whether FoMO has sufficient predictive power to be an adequate and common explanatory variable for both social media (SM) use and alcohol consumption in young college students; and, to evaluate FoMO as a mediating variable in the relationship between self-esteem and neuroticism with these behaviors. Method: 959 adults aged 18 to 40 participated (M = 22.34; SD = 3.99). The following variables were assessed: FoMO; hours spent on SM and PSMU; alcohol consumption, alcohol-related problems, and binge drinking (BD) frequency; anxiety, depression, self-esteem, basic psychological needs (BPNs) satisfaction; and personality traits (neuroticism, extraversion, agreeableness, conscientiousness, and openness). Correlations, odds rationd path analysis were estimated. Results: FoMO was related to hours spent on SM, PSMU, alcohol-related problems, and BD frequency. FoMO mediated the relationship between neuroticism and the following variables: hours spent on SM, PSMU, and, BD frequency but not between self-esteem and these variables. Conclusions: FoMO was linked to PSMU to a greater extent than excessive alcohol consumption. Future mediation models involving FoMO and these variables should include neuroticism rather than self-esteem.